2020
DOI: 10.4236/aim.2020.103009
|View full text |Cite
|
Sign up to set email alerts
|

Prime Enzymatic Exocellular Background of <i>Lysinibacillus louembei</i>

Abstract: Many high-reading journals reject several studies based on the basic aspects of microbiology by forgetting that this could open doors and windows of great scientific discoveries. A new spore-forming bacteria species called Lysinibacillus louembei has been previously discovered in our research unit. This new study aims to assess a real enzymatic machine produced with such bacteria. Using agarose mixed with half skimmed milk, LB medium supplemented with tween 20, Olive oil, egg yolk, cellulose, casein, pectin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…As per reported by Kaya-Ongoto et al (27) few studies have been shown that Lysinibacillus genera have possesses several enzymatic activities including lipolytic, proteolytic, cellulolytic, pectinolytic and amylolytic activities (16). Many lipase producing bacterial strains were isolated from diverse genera such as Bacillus (the most predominant), Pseudomonas, Serratia, Lysinibacillus, Cronobacter, Cellulosimicrobium (former Oerskovia) and Klebsiella sp, as per studies carried by Caterina Tomulescu et al (28).…”
Section: Discussionmentioning
confidence: 84%
“…As per reported by Kaya-Ongoto et al (27) few studies have been shown that Lysinibacillus genera have possesses several enzymatic activities including lipolytic, proteolytic, cellulolytic, pectinolytic and amylolytic activities (16). Many lipase producing bacterial strains were isolated from diverse genera such as Bacillus (the most predominant), Pseudomonas, Serratia, Lysinibacillus, Cronobacter, Cellulosimicrobium (former Oerskovia) and Klebsiella sp, as per studies carried by Caterina Tomulescu et al (28).…”
Section: Discussionmentioning
confidence: 84%
“…e spore-forming bacteria like B. subtilis, B. lichenifornis, and Lysinibacillus louembei have been widely used to produce BLM [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Gram-positive bacteria are known as being efficient in producing BLM. The spore-forming bacteria like B. subtilis , B. lichenifornis , and Lysinibacillus louembei have been widely used to produce BLM [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gram positive bacteria are known as professional one in the production of BLM. The spore-forming bacteria like B. subtilis, B. lichenifornis and Lysinibacillus louembei have been widely used to produce BLM [3941].…”
Section: Discussionmentioning
confidence: 99%